ACCELERATING KERR-NEWMAN-NUT/ CONFORMAL FIELD THEORY CORRESPONDENCE - Irawan, Andika
In this report, a correspondence between black holes and conformal field theory was studied. The study was conducted for accelerating extreme black holes that preserved SL(2,R) timesU(1) isometry group. In this condition, space-time did not satisfy the flatness theorem, and generators form an asymptotic symmetry group (ASG). The commutation among generators satisfied Virasoro algebra. On the other hand, Virasoro algebra exists in the formulation of CFT as well, then it leads to the correspondence between black holes and conformal field theory. Thus, the thermodynamic aspects of black holes such as temperature and entropy can be studied microscopically. In this report, we studied analitycally to reproduce the Bekenstein-Hawking entropy, that is equivalent to the entropy produced through the Cardy formula.